Fiscal Constraintson Market-Oriented Reform in a Socialist Economy - Dinopoulos, Elias (IMF Working Papers; Working Paper, 1991)
This paper develops a simple two-sector model of a socialist economy, in which government revenues required for servicing external debt are obtained from taxation of the socialized sector and from import taxes. Wages and employment in the socialized sector are the outcome of Nash bargaining between the government and an import-competing labor-dominated state enterprise with domestic market power. The effects of trade liberalization, demonopolization, technical improvements, and limitations on labor's bargaining power are examined, and the implications for privatization are considered. It is shown that some combination of tax reform and debt reduction may be a precondition for market-oriented reforms.